Investigating the home advantage in the world's prestigious football leagues before and after the outbreak of COVID-19 - Ghahfarokhi, E. A.; Soroush, S.; Hasanbeigi, H. (Brazilian Journal of Futsal and Football, 2022)
The aim of this study was to evaluate the effects of the COVID-19 (absence of spectators) on the results of football teams in 5 popular leagues in the world (English Premier League, Italian Serie A, Spanish LaLiga, German Bundesliga and French Ligue 1). This research was descriptive-comparative. Therefore, the results of football teams were analyzed from the 2015/16 season to the middle of the 2019/20 season (before COVID) and the continuation of the 2019/20 season to the 2020/21 season (after COVID). The number of matches analyzed was 10,853, including 2,546 after COVID matches. The variables that were analyzed were: home Advantage, ratio of goals scored (HGSR) and ratio of goals conceded (HGCR) in home games. The results of t-test showed a significant decrease in home advantage (p=0.044) only in the German Bundesliga. In addition, in the EPL, none of the variables showed a significant difference. In the Italian, German and French leagues, HGCR increased significantly after COVID pandemic (p<0.04). In the Spanish league, HGSR showed a significant decrease (p<0.04). In this study, only the absence of spectators over home advantage was examined. Although spectators may influence the results, teams still perform better at home in the COVID pandemic duration. So, we can conclude the location of the events can be important. Also, the referees can be unfairly biased in favor of one side or another by the presence of crowds. Hence, future research may examine other factors.